2020
DOI: 10.3390/molecules25040878
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Pharmacokinetic Profile of a Promising Antibacterial Agent: 22-(2-Amino-phenylsulfanyl)-22-Deoxypleuromutilin

Abstract: A new pleuromutilin derivative, 22-(2-amino-phenylsulfanyl)-22-deoxypleuromutilin (amphenmulin), has been synthesized and proved excellent in vitro and in vivo efficacy than that of tiamulin against methicillin-resistant Staphylococcus aureus (MRSA), suggesting this compound may lead to a promising antibacterial agent to treat MRSA infections. In this study, the effectiveness and safety of amphenmulin were further investigated. Amphenmulin showed excellent antibacterial activity against MRSA (minimal inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Following exposure to 2× MIC and 4× MIC for 2 h, the PAE of compound 9 was 1.54 and 1.71 h. These results indicated that compound 9 displayed a concentration-independent PAE and possessed a similar PAE as tiamulin (2× MIC for 1.65 h and 4× MIC for 2.04 h) [27]. Thus, the results of the PAE might guide us in the rational use of compound 9 in future clinical practice and the evaluation of adverse reactions of antibiotics and combined use [25]. The results are presented in terms of the log 10 CFU/mL change.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 74%
See 1 more Smart Citation
“…Following exposure to 2× MIC and 4× MIC for 2 h, the PAE of compound 9 was 1.54 and 1.71 h. These results indicated that compound 9 displayed a concentration-independent PAE and possessed a similar PAE as tiamulin (2× MIC for 1.65 h and 4× MIC for 2.04 h) [27]. Thus, the results of the PAE might guide us in the rational use of compound 9 in future clinical practice and the evaluation of adverse reactions of antibiotics and combined use [25]. The results are presented in terms of the log 10 CFU/mL change.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 74%
“…As an important, well-established pharmacodynamic parameter, post-antibiotic effect (PAE) refers to a period of time after the antibiotic has been completely removed from the culture medium with continual inhibition of bacterial growth [25]. A long PAE antibiotic might have a favorable outcome in clinical use, such as the ability to have to a lessfrequent interval of administration, potentially reduced treatment cost and inhibition of the development of drug resistance [26].…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%
“…Valnemulin treatment in murine RAW 264.7 macrophages also significantly inhibited LPS-induced production of inflammatory mediators, including nitric oxide, prostaglandin E 2 , TNF-α, and IL-6 [ 37 ]. Likewise, significantly reduced TNF-α, IL-6, and CCL-2 serum levels were observed in a methicillin-resistant Staphylococcus aureus wound infection mouse model following treatment with amphenmulin, a pleuromutilin derivative currently in development for veterinary use [ 38 ]; due to the model used, however, further studies are needed to determine if these effects were the direct result of anti-inflammatory activity, an indirect consequence of antimicrobial activity, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium with a broad spectrum of drug resistance 1 , 2 . The prevalence of MRSA infection had become a serious medical problem in hospital and community settings 3 .…”
Section: Introductionmentioning
confidence: 99%